2014
DOI: 10.1089/cyber.2012.0629
|View full text |Cite
|
Sign up to set email alerts
|

Video Game Use and Cognitive Performance: Does It Vary with the Presence of Problematic Video Game Use?

Abstract: Action video game players have been found to outperform nonplayers on a variety of cognitive tasks. However, several failures to replicate these video game player advantages have indicated that this relationship may not be straightforward. Moreover, despite the discovery that problematic video game players do not appear to demonstrate the same superior performance as nonproblematic video game players in relation to multiple object tracking paradigms, this has not been investigated for other tasks. Consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Since we did not find any differences between VGP and NVGP on the behavioral level, one might conclude that longtime action video gaming had no influence on cognitive performance. There have been various studies, which also found no beneficial effects of AVG experience on cognitive performance (e.g., Collins & Freeman, ; Van Ravenzwaaij, Boekel, Forstmann, Ratcliff, & Wagenmakers, ) and we suppose that a great number of similar studies have gone unreported due to publication bias. On the other hand, there have also been many studies reporting cognitive advantages for action video gamers—as mentioned in the introduction part of this paper (section ).…”
Section: Discussionmentioning
confidence: 84%
“…Since we did not find any differences between VGP and NVGP on the behavioral level, one might conclude that longtime action video gaming had no influence on cognitive performance. There have been various studies, which also found no beneficial effects of AVG experience on cognitive performance (e.g., Collins & Freeman, ; Van Ravenzwaaij, Boekel, Forstmann, Ratcliff, & Wagenmakers, ) and we suppose that a great number of similar studies have gone unreported due to publication bias. On the other hand, there have also been many studies reporting cognitive advantages for action video gamers—as mentioned in the introduction part of this paper (section ).…”
Section: Discussionmentioning
confidence: 84%
“…Studies involving clinical populations were systematically excluded (R. W. Li et al, 2011), as were studies comparing action video game players to particular populations such as musicians or bilinguals (Bergstrom, Howard, & Howard, 2012;Bialystok, 2006). Another study was excluded because we could not obtain the data in format corresponding to our action video game players selection criteria (Collins & Freeman, 2014).…”
Section: Selection Criteriamentioning
confidence: 99%
“…Although there are only a few studies investigating this, most of them have found significant associations between action game play and flexibility, with videogame players showing lower switching cost than non-videogame players (Colzato 2010;Dobrowolski et al 2015;Green et al 2012;Hartanto et al 2016;Karle et al 2010;Strobach et al 2012). To our knowledge, only three studies have failed to find differences between action videogame players and non-players (i.e., Cain et al 2012;Collins and Freeman 2014;Dobrowolski et al 2015). However, the study from Dobrowolski et al (2015) is discussed separately below, as it distinguishes between different types of videogames and yields different results.…”
Section: Results and Preliminary Discussionmentioning
confidence: 96%